DEVELOPMENT OF SIMULATION-BASED SCHEDULER FOR BACK-END STAGES IN SEMICONDUCTOR FOUNDRY - Moon, Dug Hee; Sim, Jaehun; Ro, Wonju; Kim, Dong Ok (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Changwon, Republic of Korea As one of the fastest growing industries, the manufacturing processes of semiconductors have become more complex, given the need to flexibly and rapidly respond to various customer requirements. Due to the complex manufacturing processes, a customized scheduling system is required to efficiently and effectively sequence and assign the jobs to the proper machines in the front-end and back-end manufacturing processes. Compared with the technological advancements achieved in the front-end manufacturing process, the back-end manufacturing process has not been sufficiently developed technologically. In the back-end manufacturing foundry, the reduction of the turnaround time is viewed as an important step toward competing with global competitors in the current business environment. Thus, this study utilizes a simulation approach to develop a customized scheduler with customized dispatching rules, mainly focusing on a die attach process and a wire bond process, which are critical stages in the back-end manufacturing process. Two dispatching rules have been suggested with the main objective of turnaround time minimization. The first rule (Rule 1) relates to the wire bond process, while the second rule (Rule 2) relates to the die attach process. Finally, a combination of both rules is also suggested. The results of the simulation experiments demonstrate that the proposed combined rule outperforms the other popular dispatching rules in the back-end manufacturing process with regard to production rate, turnaround time, mean tardiness, and tardy rate. Furthermore, this study investigates the suitable production amount of the developed scheduler to satisfy manufacturing constraints.